Collecting Virtual and Augmented Reality in the Twenty-First Century Library. Issue 2 (3rd July 2019) - Hannah, Matthew; Huber, Sarah; Matei, Sorin Adam
Abstract: In this paper, we discuss possible pedagogical applications for virtual and augmented reality (VR and AR), within a humanities/social sciences curriculum, articulating a critical need for academic libraries to collect and curate 3D objects. We contend that building infrastructure is critical to keep pace with innovative pedagogies and scholarship. We offer theoretical avenues for libraries to build a repository 3D object files to be used in VR and AR tools and sketch some anticipated challenges. To build an infrastructure to support VR/AR collections, we have collaborated with College of Liberal Arts to pilot a program in which Libraries and CLA faculty work together to bring VR/AR into liberal arts curricula.